2020
DOI: 10.1136/gpsych-2020-100276
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Urdu version of the Hospital Anxiety and Depression Scale (HADS) among pregnant women in Abbottabad, Pakistan

Abstract: BackgroundThe Hospital Anxiety and Depression Scale (HADS) is a widely used instrument to measure anxiety and depression symptoms.AimsThis study aimed to translate, validate and test the applicability of the Urdu version of the Hospital Anxiety and Depression Scale (HADS/UV) among pregnant women.MethodsThe original English version of the HADS was translated into Urdu by three bilingual experts and retranslated to English using the forward–backward approach. The questionnaire was administered to a sample of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…EFA showed a one-factor structure to be more interpretable than a two-factor structure, while CFA showed a one-factor structure, excluding items 11 and 14, to have a good fit (CFI = 0.95 and RMSEA = 0.05). Lodhi et al 16 performed an EFA of 200 pregnant Pakistani women. They identified a two-factor structure where items 3, 6, 7, and 13 had dual loadings while item 14 did not belong to either factor with a low factor loading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EFA showed a one-factor structure to be more interpretable than a two-factor structure, while CFA showed a one-factor structure, excluding items 11 and 14, to have a good fit (CFI = 0.95 and RMSEA = 0.05). Lodhi et al 16 performed an EFA of 200 pregnant Pakistani women. They identified a two-factor structure where items 3, 6, 7, and 13 had dual loadings while item 14 did not belong to either factor with a low factor loading.…”
Section: Discussionmentioning
confidence: 99%
“…Waqas et al 20 found a one-factor structure using both EFA and CFA with the same dataset of 500 pregnant Pakistani women. Lodhi et al 16 reported that EFA of 200 pregnant Pakistani women resulted in an ambiguous two-factor structure. These inconsistencies indicate that further studies are required to determine the factor structure of the HADS in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our rodent model of neuropathic pain, the SNL model was operated by ligation of spinal L5 and L6, and after 14 days, the microglialderived inflammatory response accelerated nerve injury and developed to pain states [20,21]. In human and animal studies, many studies have found that patients with pain are more likely to develop anxiety-like behaviours [22][23][24][25][26]. Periphery nerve injury sensitized spinally mediated transmission of messengers of pain to a higher brain control center, including lateral parabrachial area, caudal ventrolateral medulla, and periaqueductal grey matter.…”
Section: Discussionmentioning
confidence: 99%
“…A score of 0–7 is considered as normal, 8–10 as borderline and 11–21 as either anxious or depressed. Cronbach's alpha coefficient has been found to be 0.82 for the anxiety subscale and 0.64 for the depression subscale (Lodhi et al, 2020); (2) Health‐related quality of life using the SF‐36 MCS, 36‐item Short Form Survey (SF‐36) (Ayuso‐Mateos et al, 1999). Total score on each SF‐36 subscale ranges between 0 and 100, with 0 indicating the lowest level of function and 100 the highest level of function (Cronbach's alpha value of 0.9) (Bunevicius, 2017); (3) Perception of pain, evaluated using the short questionnaire for assessment of pain (BPI) (de Andrés Ares et al, 2015), consists of four items that are scored from 0 (no pain) to 10 (worst possible pain), whereas the functional interference section consists of seven items that are scored from 0 (no interference) to 10 (complete interference) (Cronbach's alpha value of 0.91) (Jelsness‐Jørgensen et al, 2016); and (4) Fatigue, evaluated using the Fatigue Scale (FACIT) (Hewlett et al, 2011), the scale range is 0–52, with 0 being the worst possible score and 52 being the best possible score indicating no fatigue (Cronbach's alpha value of 0.92) (MontanI et al, 2018).…”
Section: Methodsmentioning
confidence: 99%